Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.